Kidney stone analysis techniques and the role of major and trace elements on their pathogenesis: a review - Singh, Vivek K. (Biophys Rev, 2014)
Kidney stone disease is a polygenic and multifactorial disorder with a worldwide distribution, and its incidence and prevalence are increasing. Although significant progress has been made in recent years towards identifying the specific factors that contribute to the formation of kidney stone, many questions on the pathogenesis of kidney stones remain partially or completely unanswered. However, none of the proposed mechanisms specifically consider the role(s) of the trace elements and, consequently, the contribution of trace constituents to the pathogenesis of kidney stones remains unclear and under debate. The findings of some studies seem to support a role for some major and trace elements in the initiation of stone crystallization, including as a nucleus or nidus for the formation of the stone or simply as a contaminant of the stone structure. Thus, the analysis of kidney stones is an important component of investigations on nephrolithiasis in order to understand the role of trace constituents in the formation of kidney stones and to formulate future strategies for the treatment and prevention of stone formation and its recurrence. The aim of this review is to compare and evaluate the methods/procedures commonly used in the analysis of urinary calculi. We also highlight the role of major and trace elements in the pathogenesis of kidney stones.